Induction and initial characterization of a new Helicobacter pylori prophage - Ferreira, Rute Vanessa Novais (2021)
Helicobacter pylori is a Gram-negative bacterium that colonizes the stomach and it is considered one of the major human pathogens. Current treatments include a set of antibiotics with decreasing eradication rates, mainly due to the increase in the appearance of antibiotic-resistant strains. Bacterio(phages) have emerged in recent years as an effective alternative to fight bacterial infections. For therapeutic purposes, only strictly lytic phages have been considered, but the number of H. pylori lytic phages identified so far is scarce. Phages can be reversibly integrated into the host bacterial genome as prophages and, in the case of H. pylori, previous studies have identified the integrase gene in about 20 % of the genomes. Here, we screened the presence of prophages genes (integrases and holin) in a set of 73 H. pylori Portuguese clinical strains by PCR assays. The genomes of positive strains were sequenced and prophages content was analysed using the PHASTER tool. Employing UV radiation for 60 seconds as an inducing agent, we were able to isolate a new H. pylori prophage from the lysate of clinical strain 11057, using another H. pylori (11507) as the indicator host. The prophage forms small uniform plaques (1mm diameter) in five of the 76 H. pylori strains tested. TEM analysis revealed that the phage belongs to the Podoviridae family. Additionally, this phage proved to be stable in a temperature range of -20 to 37 °C and between pH values of 3 and 11, suggesting good stability in the gastric environment. In vitro efficacy tests demonstrated that the phage was capable of maintaining the H. pylori population at low levels for up to 24h post-infection with MOIs of 0.1 and 1. Overall, this phage seems to hold a great therapeutic potential against H. pylori gastric infections, if safety measures are guaranteed.